Tailoring properties of porous Poly (vinylidene fluoride) scaffold through nano-sized 58s bioactive glass. Issue 1 (2nd January 2016) - Shuai, Cijun; Huang, Wei; Feng, Pei; Gao, Chengde; Shuai, Xiong; Xiao, Tao; Deng, Youwen; Peng, Shuping; Wu, Ping
Abstract: The biological properties of porous poly (vinylidene fluoride) (PVDF) scaffolds fabricated by selective laser sintering were tailored through nano-sized 58s bioactive glass. The results showed that 58s bioactive glass distributed evenly in the PVDF matrix. There were some exposed particles on the surface which provided attachment sites for biological response. It was confirmed that the scaffolds had highly bioactivity by the formation of bone-like apatite in simulated body fluid. And the bone-like apatite became dense with the increase in 58s bioactive glass and culture time. Moreover, the scaffolds were suitable for cell adhesion and proliferation compared with the PVDF scaffolds without 58s bioactive glass. The research showed that the PVDF/58s bioactive glass scaffolds had latent application in bone tissue engineering.